2017
DOI: 10.1007/s00330-017-5068-5
|View full text |Cite
|
Sign up to set email alerts
|

Is impaired cerebral vasoreactivity an early marker of cognitive decline in multiple sclerosis patients?

Abstract: • Cerebral vasoreactivity does not differ between multiple sclerosis patients and controls. • Cerebral vasoreactivity measure is linked to cognitive impairment in multiple sclerosis. • Cerebral vasoreactivity is linked to level of education in multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…10 studies were included in the final review [ 10 , 13 , 14 , 30 36 ]. All studies were of a fair to good quality as assessed by two independent researchers (SC and HM; See Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 studies were included in the final review [ 10 , 13 , 14 , 30 36 ]. All studies were of a fair to good quality as assessed by two independent researchers (SC and HM; See Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Research was conducted in four countries (USA n = 4, Canada n = 2, Switzerland n = 1, France n = 3). Participants in 7 of the studies had an average age of mid-to-late 60’s to early 70’s [ 10 , 13 , 30 32 , 35 , 37 ], one study investigated adults aged 30–50 years (patients mean age 39 ± 5.91 years, controls mean age 41 ± 6.38 years) [ 36 ], one study recruited adults with moyamoya disease aged over 18 years (range 29–73, mean age 40.4 years) [ 34 ], while the remaining study involved a cohort of older (mean age 63 ± 5 years) and younger adults (mean age 24 ± 3 years) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similarly, CVR impairment is associated with an increased risk of cerebral ischemia. 14 To date, few studies have investigated CVR in MS, [15][16][17] and one group showed that CVR might be reduced in MS. 18,19 It remains unclear, however, whether clinical and neuroimaging disease activity is related to CVR in MS. We also do not know whether low CVR increases the risks of brain atrophy and accumulation of demyelinating lesions. Because previous findings on CVR in MS are inconsistent and come from small studies, we checked whether CVR was impaired in MS in a larger group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…15 Similar to our findings, Metzgen et al, who measured CVR with blood oxygen level-dependent (BOLD) functional MRI (fMRI) after CO 2 inhalation, observed normal CVR in MS and did not find CVR to correlate with brain volume and WM lesion volume. 17 Those investigators showed that CVR was reduced in patients with MS and cognitive impairment, but this relationship is found in other diseases as well. 22 To date, based on arterial spin labeling (ASL) fMRI, only 1 group has reported reduced CVR in MS.…”
mentioning
confidence: 99%